Base camp: the physical and training testing protocol of the Swedish Tennis Association - Johansson, F.; Sartok, T.; Renström, P. (Medicine and Science in Tennis, 2010)
For many years, Sweden has been a tennis country of high standards, in order to stay that way the Swedish Tennis Association started a physical project in January 2007 with support from the Swedish Olympic Committee. The former head of sports Mikael Stripple together with Fredrik Johansson was in charge of the project called Base Camp. Today the new head of sports Johan Sjögren and Fredrik Johansson is continuing the work. The objective of the program was, first of all, to document how the player`s physical status was at a national junior elite level and second to improve physical capacity and prevent injuries. The long-term goal is to prepare the players physically for professional tennis at the ATP and WTA tour.